2023
DOI: 10.1149/2162-8777/acdffa
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Raman Peak Shift in Single-Crystalline Silicon-Germanium

Abstract: We demonstrate the relationship between Raman shift ω and temperature T (dω/dT) of silicon-germanium (SiGe) for Si-Si, Si-Ge, and Ge-Ge vibration modes which should be useful in local temperature evaluation of SiGe devices at submicron levels. We investigated the dω/dT of single-crystalline SiGe for Si-Si, Si-Ge, and Ge-Ge vibration modes and its dependence on the Ge fraction using variable-temperature Raman spectroscopy. We clarified that the (dω/dT)s for Si-Si, Si-Ge, and Ge-Ge are fairly constant for all si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…37,38) In order to evaluate the thermal properties of SiGe NWs, the temperature of the sample was estimated using the relation of dω/dT = -0.0178 cm −1 /K for the Ge-Ge mode of SiGe alloy. 33) We consider that dω/dT has a constant value regardless of material structure, and both size and stress do not affect the temperature measurement using dω/dT of SiGe based on the previous reports on the temperature dependence of Si NW 9,30) by Raman spectroscopy. 33) Figure 4 shows the laser power-dependent temperature of SiGe NWs and Ge substrate using the Raman shift.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38) In order to evaluate the thermal properties of SiGe NWs, the temperature of the sample was estimated using the relation of dω/dT = -0.0178 cm −1 /K for the Ge-Ge mode of SiGe alloy. 33) We consider that dω/dT has a constant value regardless of material structure, and both size and stress do not affect the temperature measurement using dω/dT of SiGe based on the previous reports on the temperature dependence of Si NW 9,30) by Raman spectroscopy. 33) Figure 4 shows the laser power-dependent temperature of SiGe NWs and Ge substrate using the Raman shift.…”
Section: Resultsmentioning
confidence: 99%
“…33) We consider that dω/dT has a constant value regardless of material structure, and both size and stress do not affect the temperature measurement using dω/dT of SiGe based on the previous reports on the temperature dependence of Si NW 9,30) by Raman spectroscopy. 33) Figure 4 shows the laser power-dependent temperature of SiGe NWs and Ge substrate using the Raman shift. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, XRD confirmed that the singlecrystalline bulk SiGe samples were in strain-free states. 25,26) In other words, the obtained lattice parameters of bulk SiGe samples are expressed by the values reported by Dismukes et al 7) We used a Raman spectrometer with a focal length of 2000 mm and high-wavenumber resolution 27) to obtain precise spectral shapes of Raman spectra of SiGe. There were 1800 mm −1 grating grooves (for the Si-Si and Si-Ge modes) and 2400 mm −1 (for the Ge-Ge mode).…”
Section: Methodsmentioning
confidence: 99%